Investigations on rf breakdown phenomenon in high gradient accelerating structures - Shao, Jiahang (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book mainly focuses on the experimental research of rf breakdown and field emission with novel methods, including triggering rf breakdown with high intensity laser and pin-shaped cathodes as well as locating field emitters with a high resolution in-situ imaging system. With these methods, this book has analyzed the power flow between cells during rf breakdown, observed the evolution of field emission during rf conditioning and the dependence of field emission on stored energy, and studied the field emitter distribution and origination. The research findings greatly expand the understanding of rf breakdown and field emission, which will in turn benefit future study into electron sources, particle accelerators, and high gradient rf devices in general. .